No evidence for linkage at candidate type 2 diabetes susceptibility loci on chromosomes 12 and 20 in United Kingdom Caucasians. - Frayling, T; McCarthy, M; Walker, M; Levy, J; O'Rahilly, S; Hitman, G; Rao, P; Bennett, A; Jones, E; Menzel, S; Ellard, S; Hattersley, A (2000)
Several studies have identified evidence for linkage between type 2 diabetes and the regions on chromosomes 12 and 20 containing the maturity-onset diabetes of the young (MODY) genes, hepatocyte nuclear factor-1alpha (HNF-1alpha) and HNF-4alpha. Two studies examining the HNF-1alpha region have demonstrated evidence for linkage at genome-wide levels of significance, whereas four studies examining the HNF-4alpha locus have resulted in evidence for linkage at more suggestive levels of significance. The demonstration of linkage to these regions in additional patient series will strengthen the evidence that susceptibility alleles exist at these loci. We therefore assessed the evidence for linkage to these regions using a large cohort of United Kingdom Caucasian type 2 diabetes-affected sibling pairs. A maximum total of 315 affected full sibling pairs were typed for microsatellite markers across the MODY regions and, in a subset of families, for markers spanning the whole of chromosome 20. Evidence for linkage was assessed using a multipoint, mode of inheritance-free method. Linkage analysis did not reveal any significant evidence for excess allele sharing at any of the regions studied. Loci contributing sibling recurrence risks, relative to the general population risk, of 1.75 and 1.25 could be excluded for the HNF-1alpha and HNF-4alpha regions, respectively. We have not confirmed in United Kingdom Caucasians the evidence for linkage previously reported on 12q and 20q. Our results highlight further the problems of replicating previous positive linkage results across different ethnic groups.